2016
DOI: 10.1093/mnras/stw965
|View full text |Cite
|
Sign up to set email alerts
|

12.2-GHz methanol maser MMB follow-up catalogue – IV. Longitude range 20°–60°

Abstract: This is the fourth and final instalment of a series of catalogues presenting 12.2-GHz methanol maser observations made towards each of the 6.7-GHz methanol masers detected in the Methanol Multibeam (MMB) survey. This final portion of the survey covers the 20 • -60 • longitude range, increasing the 12.2-GHz follow-up range to the full MMB coverage of 186 • ≥ l ≤ 60 • and |b| ≤ 2 • . Towards a total of 260 6.7-GHz MMB methanol masers (we were unable to observe five of the MMB sources in this longitude range) we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
81
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(102 citation statements)
references
References 39 publications
19
81
2
Order By: Relevance
“…The fact that the velocity range of the excited-state OH masers exceed the 12.2-GHz methanol masers is perhaps surprising given that 12.2-GHz methanol masers generally have much higher peak flux densities, and suggests that the excited-OH emission is arising from a larger volume of gas than the 12.2-GHz maser emission. Breen et al (2016) found that there was a preponderance of 12.2-GHz methanol masers with high velocity ranges within the Galactic longitude ranges of G 330 -G 340 and to a slightly lesser extent, G10 -G30. These Galactic longitude ranges correspond to significant structures in the Galaxy and it was suggested that the higher velocity ranges reflected the enhanced star formation resulting in larger relative motions that were then reflected in the individual star forming regions.…”
Section: Basic Properties Of the Different Maser Populationsmentioning
confidence: 91%
See 3 more Smart Citations
“…The fact that the velocity range of the excited-state OH masers exceed the 12.2-GHz methanol masers is perhaps surprising given that 12.2-GHz methanol masers generally have much higher peak flux densities, and suggests that the excited-OH emission is arising from a larger volume of gas than the 12.2-GHz maser emission. Breen et al (2016) found that there was a preponderance of 12.2-GHz methanol masers with high velocity ranges within the Galactic longitude ranges of G 330 -G 340 and to a slightly lesser extent, G10 -G30. These Galactic longitude ranges correspond to significant structures in the Galaxy and it was suggested that the higher velocity ranges reflected the enhanced star formation resulting in larger relative motions that were then reflected in the individual star forming regions.…”
Section: Basic Properties Of the Different Maser Populationsmentioning
confidence: 91%
“…6 shows the distributions of integrated flux densities for the 6.7-and 12.2-GHz methanol masers (these values are not available for either the water masers or the excited-state OH masers) and the overall distributions are similar to that of the peak flux densities. The most striking difference in the distributions is the preponderance of 12.2-GHz methanol masers with low integrated flux densities, dominated by a large number of weak, sin- Caswell et al 2010;Green et al 2010;Caswell et al 2011;Green et al 2012;Breen et al 2015), 12.2-GHz methanol (pink; Breen et al 2012aBreen et al ,b, 2014Breen et al , 2016, water (blue; Walsh et al 2014) and excited-state OH masers (orange; Avison et al 2016), and; (bottom) integrated flux density distribution of the 6.7-GHz methanol (magenta; Breen et al 2015) and 12.2-GHz methanol (pink; Breen et al 2012aBreen et al ,b, 2014Breen et al , 2016.…”
Section: Distribution Of Peak and Integrated Flux Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This therefore implies that although a correlation is evident, the use of one given luminosity to predict another in a host clump from the line of best fit relationship is only accurate to an order of magnitude at best, and that a 1:1 correlation of the two properties is not representative of the data. The correlation between the luminosity of the 6.7 GHz maser and secondary masing species in a host MYSO has also been studied for the targeted MMB follow-ups, so as in Breen et al (2016) and Titmarsh et al (2014Titmarsh et al ( , 2016 for the 12.2 GHz and water masers respectively, we present this for the host clumps in this sample and the SPLASH OH masers. As for the correlations between maser and host clump luminosity, the line of best fit is given by log 10 (L OH ) = (0.6 ± 0.2) log 10 (L 6.7 ) + (0.5 ± 0.7), with an average logarithmic scatter of 0.7 in 6.7 GHz luminosity and 0.4 in total OH luminosity from this line.…”
Section: Masermentioning
confidence: 95%